Irradiance encoding in the suprachiasmatic nuclei by rod and cone photoreceptors. - van Diepen, H; Ramkisoensing, A; Peirson, S; Foster, R; Meijer, J (2013)
Light information is transmitted to the central clock of the suprachiasmatic nuclei (SCN) for daily synchronization to the external solar cycle. Essential for synchronization is the capacity of SCN neurons to respond in a sustained and irradiance-dependent manner to light. Melanopsin has been considered to mediate this photosensory task of irradiance detection. By contrast, the contribution of the classical photoreceptors in irradiance encoding is less clear. Here we investigate the role of classical photoreceptors by in vivo electrophysiological responses in freely moving animals to specific wavelengths of light (UV, λmax 365 nm; blue, λmax 467 nm; and green, λmax 505 nm) in both melanopsin-deficient (Opn4(-/-)) mice and mice lacking rods and cones (rd/rd cl). Short- and long-wavelength light induced sustained irradiance-dependent responses in congenic wild-type mice (+19.6%). Unexpectedly, sustained responses to light persisted in Opn4(-/-) mice (+18.4%). These results provide unambiguous evidence that classical photoreceptors can transmit irradiance information to the SCN. In addition, at light intensities that would stimulate rod and cone photoreceptors, the SCN of rd/rd cl mice showed greatly reduced sustained responses to light (+7.8%). Collectively, our data demonstrate a role for classical photoreceptors in illuminance detection by the SCN.